P3.165 Establishing Second Generation HIV/STI-surveillance For Migrants from Sub-Saharan Africa in Germany - A Participatory Process. (13th July 2013) - Santos-Hövener, C; Hamouda, O; Koschollek, C; Charles, T; Gangarova, T; Marcus, U
Abstract : Background: Migrants from sub-Saharan Africa (MisSA) are a relevant sub-group for HIV-transmission in Germany. 10–15% of all newly diagnosed cases are MisSA, and approximately one third acquired HIV in Germany. Diagnosis is often at a late clinical stage of HIV-infection, potentially due to barriers to HIV-testing or health care in general. There is limited information on prevalence of STIs and on knowledge, attitudes, behaviours and practises (KABP) regarding sexual health. To gain a deeper understanding of MisSA's HIV/STI-prevention needs a research process was initiated. Methods: An expert meeting took place to define specific research needs as well as a research approach. Experts were defined as persons working in HIV/STI-prevention with MisSA, key-persons from MisSA-communities and HIV/STI-researchers. A working group was established to draught a potential study design for a KABP-survey with MisSA. Recommendations of the working group were appraised by four focus groups with MisSA in different cities. Results: The following guidelines for the research process were established: The research process will be participatory and MisSA have to be involved in all stages. All decisions will be evaluated by community members and an advisory board. The MisSA-community should benefit from the research. The suggested study design was a multi-centre KABP-study on sexual health. Participants will be recruited by trained peer researchers. Optional HIV/STI-testing will be offered to participants. Questionnaires will be developed in a participatory approach and be available in multiple languages depending on the respective population of MisSA. Focus group results generally supported the suggested research design. A detailed analysis of focus group discussions is still ongoing. Conclusion: To conduct HIV/STI-research that is meaningful to MisSA, it is crucial to involve community partners in the research process. This will help to address the specific needs of MisSA and also assure a better reception of the study within the community.